2000
DOI: 10.1176/appi.ajp.157.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Lost Human Capital From Early-Onset Chronic Depression

Abstract: Early-onset major depressive disorder causes substantial human capital loss, particularly for women. Detection and effective treatment of early-onset major depressive disorder may have substantial economic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(136 citation statements)
references
References 40 publications
5
122
0
5
Order By: Relevance
“…Our results are consistent with other observational studies comparing the outcomes of depressed adolescents to non-depressed adolescents. Papers by Fletcher and Ding and colleagues (Ding et al 2009; Fletcher 2008), as well as earlier work (Berndt et al 2000) found that high school graduation rates and grades were lower for girls with depression compared to girls without, but they did not find similar results for boys. One piece of evidence that supports the notion that the FDA warnings were more important for girls than for boys is the evidence on suicides.…”
Section: Alternative Interpretation Of the Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results are consistent with other observational studies comparing the outcomes of depressed adolescents to non-depressed adolescents. Papers by Fletcher and Ding and colleagues (Ding et al 2009; Fletcher 2008), as well as earlier work (Berndt et al 2000) found that high school graduation rates and grades were lower for girls with depression compared to girls without, but they did not find similar results for boys. One piece of evidence that supports the notion that the FDA warnings were more important for girls than for boys is the evidence on suicides.…”
Section: Alternative Interpretation Of the Resultsmentioning
confidence: 86%
“…In adolescents, depression is associated with lower human capital investment. (Berndt et al 2000; Ding et al 2009; Fletcher, 2008). In addition to its effect on mood, depression causes restlessness, anxiety, difficulty with concentration, and feelings of worthlessness, all of which may inhibit academic performance or other aspects of human capital.…”
mentioning
confidence: 99%
“…Interfiere significativamente con el funcionamiento adaptativo de las personas afectadas y disminuye, en el caso de mujeres jóvenes, las posibilidades de realizar plenamente el potencial personal, en lo académico y lo laboral (9) .…”
Section: El Embarazo No Deseado Un Factor De Riesgo Para Depresiónunclassified
“…La tasa prevalente de la depresión ha ido en aumento, sobre todo en la franja etérea de adolescentes y adultos jóvenes (9,10) El objetivo de este trabajo radica en establecer si existe asociación entre la presentación del trastorno depresivo y la edad del paciente, específicamente si este es mayor o menor de 45 años, y de esta manera identificar los elementos que podrían guiar el médico psiquiatra hacia el diagnóstico y posibles causas de los trastornos, así como identificar a la población de riesgo para apuntar a la prevención mediante técnicas acordes a ese grupo etario.…”
Section: Introduccionunclassified